Prednisolone versus antihistamine for allergic rhinitis: No significant difference found in randomized trial - Carl Skröder; Laila Hellkvist; Ulla Westin; Pernilla Sahlstrand‐Johnsson; Kerstin Hansson; Agneta Karlsson; Åslög Dahl; Leif Bjermer; Lars Olaf Cardell (Clinical and Translational Allergy)
Abstract Background Seasonal allergic rhinitis (AR) impacts public health by affecting work productivity and quality of life. The Swedish tree pollen season starts in February with alder and hazel pollination, followed by birch and ends with oak in May. Systemic corticosteroids are often prescribed when topical treatments fail, despite limited evidence supporting their efficacy. Objective To compare the effectiveness of prednisolone tablets versus antihistamine tablets in reducing symptoms and medication usage in patients with moderate to severe tree pollen‐induced AR. Methods This interventional single‐center, double‐blinded randomized trial included 34 patients. Treatment was initiated, and symptoms were registered during the tree pollen season. The two groups received either prednisolone tablets (20 mg) or ebastine tablets (20 mg) for 7 days. Treatment effects were evaluated by comparing daily symptom scores, use of topical medication, and a combined symptom‐medical score between the groups. Quality of life was recorded at the start and after 3 weeks. Results Both interventions demonstrated efficacy in enhancing quality of life metrics. The area under the curve (AUC) for the combined symptom severity and medication usage score averaged 34.0 (SD = 19.1, 95% CI = 24.5–43.4) in the group treated with prednisolone. This was marginally lower than the control group, with an AUC of 32.6 (SD = 13.2, 95% CI = 25.6–39.7). The difference was not statistically significant (p = 0.80). Both groups exhibited only mild adverse events, which were statistically comparable in frequency and severity. Conclusions Prednisolone tablets did not show superior efficacy over antihistamine tablets in reducing symptoms or medication usage in tree pollen‐induced AR. These results suggest that systemic corticosteroids may not provide additional benefits over antihistamines, and clinicians should prioritize individualized treatment based on patient preferences and tolerability.